Cortical auditory-evoked potential as a biomarker of central auditory maturation in term and preterm infants during the first 3 months - Didoné, Dayane Domeneghini; Oliveira, Lilian Sanches; Durante, Alessandra Spada; Almeida, Kátia de; Garcia, Michele Vargas; Riesgo, Rudimar dos Santos; Sleifer, Pricila (Clinics, 2021)
OBJECTIVES: To analyze central auditory maturation in term and preterm infants during the first 3 months of life by comparing the latency and amplitude of cortical auditory-evoked potential at different frequencies. METHODS: In this study, 17 term and 18 preterm infants were examined; all had tested positive on the neonatal hearing screening test. Cortical auditory potential was investigated during the first and third months of life. The response of the cortical auditory-evoked potential was investigated at frequencies of 500, 1000, 2000, and 4000 Hz. The latency and amplitude of the cortical response were automatically detected and manually analyzed by three researchers with experience in electrophysiology. The results were compared using analysis of variance and the Bonferroni test. A significance level of 5% was used for all analyses. RESULTS: Latency valu es of cortical auditory-evoked potential in the first month of birth were significantly higher than those in the third month, and latency values of the preterm group were higher than those of the term group, regardless of the frequency and time of evaluation. In general, the latency of the cortical auditory-evoked potential was higher at high frequencies. Amplitude values in the third month of life were significantly higher than those in the first month for term and preterm infants. CONCLUSION: Central auditory maturation was observed in both groups but with different results between those born at term and preterm, with latencies of cortical auditory-evoked potential higher for the preterm group and at high frequencies.